A comparative study of Canadian and Scottish students' perspectives on health, the body and the physical education curriculum: the challenge of 'doing' critical. Issue 1 (2nd January 2018) - Gray, Shirley; MacIsaac, Sarah; Harvey, William J.
ABSTRACT: Physical education (PE) curricula in many countries explicitly task teachers with the responsibility to support the health of their pupils. However, there are concerns that a prevailing 'healthism' discourse is influencing how PE curricula are enacted. Although we know something about how PE teachers understand and 'teach' health, little is known about the perspectives of student PE teachers. We carried out semi-structured interviews with PE student teachers from Canada and Scotland to explore how they conceptualised health and the body. Furthermore, we investigated how their understandings of health and the body influenced their perceptions of teaching 'health' in their respective PE contexts. Our post-structural analysis demonstrates how the students' Initial Teacher Education (ITE) contexts influenced their perceptions of where the responsibility lies for addressing the health of young people. These different perceptions have enabled and constrained practice in various ways. The Scottish students critically deconstructed dominant healthism and obesity discourses but this process did not result in the articulation of critical practice. The Canadian students were less likely to engage in critical inquiry but evidenced creativity and divergent thinking in relation to how they would integrate health outcomes in their teaching. We conclude by exploring the implications of these findings for ITE programs by advocating an applied approach to critical inquiry.